(untitled) (Caderno de Ciências Navais, 2026)
This article analyzes historical facts and evidence that contribute to understanding the causes of the Suez Conflict (1956) between Egypt, the United Kingdom, and France, limiting the scope of the research to the 20th century. The authors use a multidimensional approach supported by contemporary theories that help understand the processes leading to armed conflict outbreaks to achieve this goal. It is demonstrated that the situation presented in Suez – which includes not only a political background but a multifaceted one – was elucidated by Polemology, which demonstrates the classic complexity of international relations and the enormous variety of interests involved in these relations.